Deaf Sign-Language Using Patients' Experiences in Health Emergencies in Wales: Perspectives for Improving Interactions - Foltz, Anouschka; Shank, Christopher (Frontiers in Communication, 2020)
Health emergency services are a critical aspect of any health care system. They need to respond quickly and efficiently, especially in life-threatening situations. In a 2019 scoping study on health and access to health care services in the Deaf community in Wales, we noted the poor perception of health emergency services by this community. In this perspective article, we present reflections and opinions on health emergency services expressed by members of the Welsh Deaf community, with a focus on texting 999 and the availability of British Sign Language interpreters on short notice. We also present our viewpoint to deal with the issues in both settings.